Death by Folklore: Case Closed? - Ellis, Bill (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
My original essay “Death by Folklore” was written soon after the 1982 murders of teenagers Annette Cooper and Todd Schultz in an area of Southeastern Ohio plagued by rumors of Satanic cults. I argued that the killings and the local reaction to them could be understood as acts of ostension, possibly criminal acts or, more likely, acts of interpreting ambiguous events in terms of familiar legends about Satanism. Since then, the original defendant has been exonerated, and a convict has confessed to being the actual murderer, which he says was the result of an unmeditated impulse with no folklore relevance. So, was my article irrelevant to the crime? The essay surveys new information uncovered through investigative journalism and criminal justice research, and concludes that ostension, in its current sense, remains the best theoretical tool for understanding the murders’ cultural significance.